Correlation Between English Motivation and Speaking Proficiency: A Mixed-Methods Study at Shafta Senior High - Heriyanto, Nahlu Hasbi (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2024)
This study investigates the correlation between students' motivation in learning English and their speaking proficiency at Shafta Senior High School. Utilizing a mixed-methods approach, the research combines quantitative data from questionnaires and qualitative insights from semi-structured interviews to explore how both intrinsic and extrinsic motivational factors influence speaking skills. The findings reveal a significant positive relationship, highlighting the crucial role of motivation in enhancing speaking proficiency. The study offers practical implications for educators, including strategies to foster motivation, encourage regular practice, and provide supportive feedback. Recommendations for future research include expanding the sample size, exploring additional influencing factors, and conducting longitudinal studies.